(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article talks about corpus linguistics, particularly parallel corpus, which is currently one of the most developed fields in world linguistics. The literary text and its translated text in another language contain ideas about the difficulties that arise in the translation process. In particular, changes in the delivery of the original to readers of other languages in the source language and translation texts are covered in detail.